Accelerated Nodulosis in a Patient With Rheumatoid Arthritis - Ayşe Ünal ENGİNAR and Hakan NUR and Erdal GİLGİL and Cahit KAÇAR (Archives of Rheumatology, 2019)
In patients with rheumatoid arthritis (RA), subcutaneous nodules are the most frequently seen extra-articular findings that are seen in areas of extensor pressure. In this article, we present the case of a RA patient with accelerated nodulosis that started with the use of methotrexate and exacerbated with etanercept and leflunomide treatment.